Relationship Between Red Blood Cell Indices and Myxomatous Mitral Valve Disease in Small‐Breed Dogs: A Retrospective Study - Eui‐Joo Hong; Yunho Jeong; Ju‐Hyun An; Sooyoung Choi; Jin‐Young Chung; Jin‐Ok Ahn (Veterinary Medicine and Science)
ABSTRACT Background Red blood cell (RBC) indices provide information on the size and haemoglobin content of erythrocytes. The RBC distribution width (RDW) is an index of size variability of the circulating RBC population. The correlation between various diseases and RDW in dogs has been demonstrated. Some studies have evaluated RDW in dogs with myxomatous mitral valve disease (MMVD), and conflicting results have been reported. Objectives We aimed to evaluate the association between RBC indices, complete blood cell counts (CBC), and serum biochemical and echocardiographic variables in small‐breed dogs with MMVD. Methods RBC indices, CBC, and serum biochemical and echocardiographic variables were retrospectively investigated in 102 client‐owned dogs with MMVD at various disease stages. Results RBC indices were not statistically significant among groups (control group, compensated group, decompensated group). RDW had a significant positive correlation with haematocrit (Hct) (correlation coefficient, 0.452) and a negative correlation with MCH (correlation coefficient, −0.498) and MCV (correlation coefficient, −0.357). The end‐diastolic volume index, fractional shortening (%), and left atrial‐anteroposterior diameter normalised for body weight were echocardiographic variables that affected MMVD severity. Conclusions We observed no correlation between RBC indices and MMVD. However, conflicting results have been reported in several other studies; thus, further studies should be considered.